Acústica urbana de Umuarama : avaliação e metodologia para procedimento de reurbanização - Marques, Caroline Salgueiro da Purificação (2010)
One of the environmental problems, in constant growth, is the urban traffic noise, a major source of noise pollution at Umuarama City, PR, Brazil. The re-urbanization is an urban management strategy that enables the regeneration of a region or a city, to improve the quality of life of local residents. The objective of this applied research is to study its urban acoustics on a scale of intervention and redevelopment, through two case studies, identified and classified as sensitive and industrial zone, comprising the stretches of Maringa Avenue, and PR323 Highway, respectively. For analysis of sound environments, a systematization of specific analysis was developed, including comparative evaluation of the noise level, within the established limits by Brazilian and Portuguese current regulations, in addition to the acoustic mapping using SoundPLAN® software. The new interpretative parameters used in this study, related to qualitative and quantitative acoustic standards, in urban planning, for the land use and occupation, must appears from urban readings and analyzes that organize their identity and acoustic comfort on the sound urban landscape composition.